Interdisciplinary assessment and management of a patient with a fibrous gingival enlargement of unknown origin: A case report - Anna Greta Barbe; Gabriele Röhrig; Lena Hieggelke; Michael Johannes Noack; Sonja Henny Maria Derman (Clinical Case Reports, 2020)
Abstract A gingival enlargement of unclear cause could only be diagnosed after interdisciplinary cooperation as plasma cell gingivitis of unknown origin. Interdisciplinary approaches remain crucial when diagnosing rare gum diseases.